Shared decision-making and sense of empowerment of teachers - Atienza, Benita M. (2006)
This study attempted to determine the extent of involvement of teachers in the decision-making process within a school setting and correlate it with the teachers' sense of empowerment. 240 teachers were given two sets of questionnaires with one measuring their involvement in decision-making and the other measuring their sense of empowerment. The responses were analyzed statistically to determine the actual and desired involvement in decision-making and sense of empowerment. Results showed that the actual participating behavior of the teachers when it comes to decision-making did not meet their desired level of participation or involvement. Increasing their level of participation does not immediately result to increasing their sense of empowerment. Other considerations should be accounted to empower the teachers.